Corporate Social Responsibility and Greenwashing as business strategies: effects on the environment. Textile industry case - Córdoba Cubero, María (Observatorio Medioambiental, 2021)
Companies nowadays have a direct impact on the social and environmental surroundings through their actions, which is the reason why it is crucial/important/essential for business ethics and responsibility to be able to assume the environmental problems that are produced and to try to stop and mitigate/reduce them. Many of the business practices undertaken by important corporations give an image of respect and care for the environment. In many cases, this perception is just a way of engaging the consumer’s attention. In practice, companies are not as tipo companies are not as environmentallyfriendly and damage the environment directly. One of the points that should be taken into consideration to change this vision could be advocate to sustainable business development based on sustainable development goals. All of these ideas will come together in this work to show how actions, campaigns or products that are beneficial to society and the environment can be carried out without putting resources and the environment at risk.